Transiciones Instituciones y subjetividades en los inicios de los estudios universitarios - Vercellino, Soledad; Pogré, Paula (Aperturas, 2023)
The transition from secondary school to university involves multiple problematic dimensions if it is considered as a transition for people who enter the dynamics of higher education. The authors of this book approach this trajectory from different points of view: the experience of the students, university policies and teaching practices aimed at ensuring the right to enter and remain in each institution, and the existence of exclusion/inclusion factors that determine situations of vulnerability and intersectional oppression. In all cases, however, the assumption on which the works gathered here operate is the necessary recognition of the plural character of students and of the subjective processes involved in the beginning of university studies. Originating in the international congress "University Admissions and Entrants", held at the Universidad Nacional de RÍo Negro in 2021, this publication offers nineteen articles with reflections and contemporary experiences developed in universities in Peru, Argentina, Uruguay, Brazil, Chile and France.